Demystifying failed VMAT PSQA measurements with ArcCHECK. (October 2017) - Kinsella, Paul; McClean, Brendan; Leon-Vintro, Luis
Abstract : A means of reducing Patient Specific QA (PSQA) measurements for VMAT is currently a popular topic due to the resource burden it generates. The reluctance to reduce PSQA may be due to the difficulty in identifying the cause/s of plans that fail. Plans may fail due to a number of potential factors caused by the TPS, linac or measurement device. The goal of this study was to uncover the reason/s why a selection of VMAT plans have failed. PSQA was performed with SNC ArcCHECK. Five failing plans and two passing plans were analysed. The control points for each plan were broken up into separate static fields. The fields were delivered to ArcCHECK and compared to the TPS using a Python program. Dose-differences were tracked field-by-field for each diode and categorised according to the location of the diode to the beam: In-field, penumbra and out-of-field. A composite measurement of individual control point fields compared with the conventional PSQA measurement showed minimal difference indicating that the reason for PSQA fail was not due to dynamic delivery. Dose differences due to the out-of-field component had the greatest impact on the overall pass-rates. The latest version of the SNC Patient software provides corrections for diode over-response out-of-field and was investigated as a potential solution. The impact of applying the correction resulted in all previously failing plans passing. Deconstructing PSQA measurements identified out-of-field dose differences as the main cause of plans failing. The results of this study indicate the new out-of-beam correction should be applied.